Remember [videorecording (DVD)] - Plummer, Christopher; Landau, Martin, 1928-2017; Norris, Dean; Prochnow, Jürgen (Lionsgate, 2016)
A suspense-filled story of Zev, an Auschwitz survivor who discovers that the Nazi guard who murdered his family some seventy years ago is living in America under an assumed identity. With the aid of a friend, Zev sets out on a gripping journey that tests both his will and his fading memory as it brings him closer to the retribution he seeks.